The relationship between pollen monodiets and the activities of proteolytic systems in the fat body and hemolymph of honeybee workers - Maciej Sylwester Bryś; Krzysztof Olszewski; Aneta Strachecka (PLoS ONE, 2025)
The homogenization of landscapes through the introduction of large-scale farms, the decline of biodiversity conditioned by high summer temperatures and dry weather, as well as the expansion of alien species determine the monodiet feeding of honeybees. In this study, we investigated the effect of monopollen feeding regimens (containing hazel, rapeseed, pine, buckwheat, Phacelia, and goldenrod) on the activity of the proteolytic system in the tergite 3, tergite 5 or sternite apian fat body, and hemolymph. We showed that pollen from rapeseed, Phacelia, buckwheat, and goldenrod increased the activities of acidic, neutral, and alkaline proteases and their inhibitors in the fat body and hemolymph when compared to the group fed with sugar candy only. The activities of proteases and their inhibitors in bees fed with pollen from hazel and pine were usually higher compared to the activities of honeybees fed with sugar candy only, but lower than in workers fed sugar candy with the pollen of entomophilous plants. Moreover, when comparing the proteolytic system activity between localizations/segments, the highest values were observed in tergite 5, regardless of what age the bees were and whether they were fed candy with added pollen. It is important to understand the impact of individual types of pollen in the context of potential future monodiets. Furthermore, the beneficial impact of Phacelia pollen to drive the rise of protease and protease inhibitor activities, helping to counteract negative environmental factors, can be supported by introducing, for example, flower mixtures for the insects or pollen-supplemented sugar candies for bees during periods without access to pollen.